CORRELATION BETWEEN POLYMORPHISMS OF FOXP3 T-REGULATORY PROMOTOR GENE WITH TGF-β IN PATIENTS WITH GRAVES’ DISEASE - ELVIRA, DWITYA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of this study is to prove that there are Forkhead Box P3 (FOXP3) T-regulator promoter polymorphisms in Graves’ disease and to analyze the association between FOXP3 T-regulator promoter polymorphisms with transforming growth factor (TGF)-β levels. Methods: This study was an observational study with cross-sectional comparative study design. Consecutive sampling was conducted in patients with Graves’ disease who came to the outpatient clinic and treated in Dr. M. Djamil Hospital, Padang. Blood sampling was performed on 30 Graves’ subjects and 30 control subjects based on inclusion and exclusion criteria. DNA isolation, primary construction, and polymorphism identification by polymerase chain reaction method and blood sample examination by enzyme-linked immunosorbent assay techniques method for TGF-β examination were performed in this study. Results: The results of this study obtained the most age of patients with Graves’ disease is 30–40 years with the female gender. Graves’ patient group was found to have 86.7% of single nucleotide polymorphisms (SNP) rs3761548 polymorphism, and 61.3% had SNP rs2232365 polymorphism followed by 26.7% polymorphism of SNP rs3761547 and rs3761549, and no SNP rs2232364 polymorphism was found. In Graves’ group, the mean value of TGF-β was 1030.01±277.64 ng/ml, significantly higher than the control group. Statistical analysis showed a significant relationship between polymorphism of the FOXP3 promoter gene and TGF-β level with p<0.05. Conclusion: This study proves that there are polymorphisms of the FOXP3 promoter gene in Graves’ patients, especially SNP rs3761548 and rs2232365. The polymorphism of the FOXP3 promoter gene has a significant association with TGF-β levels.